Ultrathin mineral interlayers regulate interfacial polymerization of polyamide nanofiltration membranes via multiple non-covalent and coordination bonding for rapid molecular separation - Yan Zhu; Danwei Huang; Hongbo Xie; Zheyuan Liu; Fei-Fei Chen; Yan Yu (Advanced Membranes, 2025)
Polyamide (PA) nanofiltration membranes have raised considerable interest in the realm of water purification. However, balancing permeability and rejection remains a critical challenge in membrane science and technology. Herein, we report that weak non-covalent hydrogen bonds and strong coordination bonds between ultrathin calcium silicate (UCS) interlayers and piperazine (PIP) powerfully control its diffusion. Theoretical calculations reveal that coordination bonds dominate PIP binding on UCS with an adsorption energy of −443.83 ​kJ ​mol−1, thereby impeding its movement. The diffusion coefficient of PIP diminishes by 14 ​% upon the incorporation of UCS, as evidenced by molecular dynamics simulations. As a consequence, a superhydrophilic, smooth, loose, and ultrathin (∼18.9 ​nm) PA separation layer is created. The as-obtained UCS-interlayered PA possesses a remarkable water permeance of 31.7 ​L ​m−2 ​h−1 ​bar−1 that is 2.2-fold higher than that of UCS-free PA, while dye rejection rates keep a high level. Furthermore, the UCS-interlayered PA demonstrates exceptional antifouling performance with a 95 ​% flux recovery ratio and long-term stability during 16-h filtration. The study highlights the pivotal role of mineral interlayers in tailoring amine monomer diffusion via multiple interfacial interactions for advanced water treatment applications.